Effects of treatment with SGLT-2 inhibitors on arginine-related cardiovascular and renal biomarkers - Geßner, Arne; Gemeinhardt, Anna; Bosch, Agnes; Kannenkeril, Dennis; Staerk, Christian; Mayr, Andreas; Fromm, Martin; Schmieder, Roland; Maas, Renke (Cardiovascular Diabetology, 2022)
Background: In patients with type 2 diabetes (T2D) sodium-glucose cotransporter 2 (SGLT-2) inhibitors improve glycaemic control as well as cardiovascular and renal outcomes. Their effects on L-arginine (Arg) related risk markers asymmetric and symmetric dimethylarginine (ADMA and SDMA) and the protective biomarker L-homoarginine (hArg) linking T2D to cardiovascular and renal disease have not yet been reported.
CRIS-Team WoS Importer:2022-01-14